1999
DOI: 10.1164/ajrccm.160.6.9901117
|View full text |Cite
|
Sign up to set email alerts
|

Serial Changes in Surfactant-associated Proteins in Lung and Serum before and after Onset of ARDS

Abstract: The goal of this study was to determine the changes that occur in surfactant-associated proteins in bronchoalveolar lavage fluid (BAL) and serum of patients at risk for ARDS and during the course of ARDS. We found that the concentrations of SP-A and SP-B were low in the BAL of patients at risk for ARDS before the onset of clinically defined lung injury, whereas the concentration of SP-D was normal. In patients with established ARDS, BAL SP-A and SP-B concentrations were low during the entire 14-d observation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
282
2
13

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(309 citation statements)
references
References 37 publications
12
282
2
13
Order By: Relevance
“…Using TNF-a as an example, the network analysis showed that in addition to proinflammatory proteins, TNF-a interacted with bacterial opsonins (complement proteins, SFTPA), mediators of apoptosis (annexin A5, annexin A1), and proteins involved in lung repair (EGFR) (30)(31)(32). This suggests that TNF-a modulates pathways involved in innate immunity and repair in the lungs, in addition to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Using TNF-a as an example, the network analysis showed that in addition to proinflammatory proteins, TNF-a interacted with bacterial opsonins (complement proteins, SFTPA), mediators of apoptosis (annexin A5, annexin A1), and proteins involved in lung repair (EGFR) (30)(31)(32). This suggests that TNF-a modulates pathways involved in innate immunity and repair in the lungs, in addition to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…When alveolar type II cells are injured, normal alveolar epithelial fluid transport and removal of alveolar edema fluid are impaired (23). Furthermore, injury to type II cells reduces the production and turnover of surfactant (12) and may also cause intrapulmonary bacterial translocation, leading to sepsis (21).…”
mentioning
confidence: 99%
“…For example, the appearance of type III procollagen peptide in edema fluid or bronchoalveolar lavage (BAL) fluid identifies patients with fatal outcomes, perhaps because it indicates that fibrosing alveolitis has begun early in the course of ALI (7,8). Abnormalities of surfactant-associated proteins in BAL fluid and plasma have also been associated with poor clinical outcomes (3,12). However, very few clinical studies have measured biochemical markers in ALI to assess pulmonary epithelial damage per se.…”
mentioning
confidence: 99%
“…Обнаружено также уменьшение содержания САБ: SP А, SP В и SP С, но не SP D [8, 91 93]. Уменьшение содержания SP А и SP В сохранялось на 14 й день после начала ОРДС [93]. При ОРДС нарушена и структурная организация ЛС: содержание больших агрегатов существенно уменьшено, а малых увеличе но [8,94,95].…”
Section: нарушения состава и свойств легочного сурфактанта при различunclassified
“…[94]. Несмотря на то, что вклад от дельных компонентов ЛС в защитные механизмы легочного по вреждения до конца не ясен, полагают, что существенное сниже ние содержания SP А [8,90,92,93], деградация SP А в легочной ткани [107] и уменьшение его опсонизирующей способности по отношению к различным патогенам вносят существенный вклад в снижение резистентности больных к гнойно септическим ос ложнениям ОРДС и ИВЛ [92,108].…”
Section: нарушения состава и свойств легочного сурфактанта при различunclassified